1999
DOI: 10.1152/jappl.1999.86.6.1778
|View full text |Cite
|
Sign up to set email alerts
|

Dextran restores albumin-inhibited surface activity of pulmonary surfactant extract

Abstract: We examined the effect of dextran (molecular weight 71,000) in counteracting the surfactant inhibitory action of plasma albumin. The surface adsorption time of 0.5 mg/ml modified natural surfactant (MNS; porcine lung extract consisting of phospholipids and hydrophobic surfactant proteins) with 7.5 mg/ml albumin decreased from 681 to 143 s by addition of dextran at a concentration of 10 mg/ml (P < 0.01). The minimum surface tension of 2.0 mg/ml MNS with 30 mg/ml albumin decreased from over 21 mN/m to below 3 mN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 27 publications
5
56
1
2
Order By: Relevance
“…For surfactants improved by addition of PEG or other polymers (12,17,19,35) to be clinically useful, our data, coupled with the observations of Campbell et al (23), indicate that careful matching of surfactant quality with the specific intraalveolar pathology may be necessary as implied by the work of Puligandla et al (22). This approach may in time significantly improve surfactant therapy for ALI/ARDS.…”
Section: Discussionsupporting
confidence: 53%
“…For surfactants improved by addition of PEG or other polymers (12,17,19,35) to be clinically useful, our data, coupled with the observations of Campbell et al (23), indicate that careful matching of surfactant quality with the specific intraalveolar pathology may be necessary as implied by the work of Puligandla et al (22). This approach may in time significantly improve surfactant therapy for ALI/ARDS.…”
Section: Discussionsupporting
confidence: 53%
“…25 mg/mL reported by Ishizaka et al (20). However, previous in vitro studies have shown that at such a concentration albumin was sufficient to inactivate a dilute lung surfactant preparation, such as the 0.5 mg/mL BLES used here (2,4).…”
Section: Methodsmentioning
confidence: 87%
“…Both in vitro (1)(2)(3)(4)(5)(6) and in vivo (7)(8)(9) trials have shown that these nonionic polymers can significantly improve the surface activity of different therapeutic lung surfactants and effectively reverse inactivation due to a variety of inhibitory substances.…”
mentioning
confidence: 99%
“…Existem alguns experimentos in vitro que demonstraram que o dextram além de apresentar um efeito protetor, potencializaria a ação do surfactante 28,29 . Alguns dos animais de nosso experimento pertenciam também a este estudo em paralelo que pretendia avaliar esta possibilidade in vivo.…”
Section: Antes De Discutirmos Esses Resultados Julgamos Pertinente Qunclassified
“…Houve quatro coelhos (peso médio de 3,00 +0,14 kg) que receberam extrato de surfactante bovino (27 mg/ml) na dose de 1 ml/kg associados com 2 ml de Dextran (peso molécula de 70.000) na concentração de 50mg/ml. O Dextran foi associado para explorar a possibilidade de aumento da atividade do surfactante conforme demonstrado em alguns estudos in vitro 28,29 Após a lavagem pulmonar, a PaO 2 média no grupo submetido à ventilação convencional associada à reposição de surfactante (CMV+S) foi de 43,6 +9,9 mmHg sem apresentar diferença (p=0,154) quando comparado com os coelhos submetidos à ventilação de alta freqüência por Em ambos os grupos, após a lavagem pulmonar, a pressão média nas vias aéreas (MAP) era a mesma (p=0,980). Entretanto, aos 15, 60 e 120 minutos após serem alocados para HFO ou CMV+S, observou-se que o grupo CMV+S apresentou uma MAP significativamente menor (p<0,001).…”
Section: Métodosunclassified